Oral anticancer therapy project: Clinical utility of a specific home care nursing programme on behalf of Italian Association of Medical Oncology (AIOM). Issue 1 (21st October 2019) - Cirillo, Massimo; Carlucci, Luciano; Legramandi, Lorenzo; Baldini, Editta; Sacco, Cosimo; Zagonel, Vittorina; Leo, Silvana; Di Fabio, Francesca; Tonini, Giuseppe; Meacci, Maria Luisa; Tartarone, Alfredo; Farci, Daniele; et al.
Abstract: Aims and objectives: To assess the effectiveness of a specific home care nursing programme in addition to standard care in patients (pts) receiving oral anticancer treatments. Background: Oral anticancer therapy present challenges for pts since treatment is a home‐based therapy. This study evaluates the potentiality of a home care nursing programme in decreasing hospital accesses for not severe toxicity. Methods: This is an open‐label, multicentre, randomised trial including pts who were receiving an anticancer oral drug. The study complies with the CONSORT checklist published in 2010. Concomitant use of radiation therapy, intravenous or metronomic therapies, or the intake of previous oral drugs was not allowed. Pts were randomly assigned to home care nursing programme (A) or standard care (B). In arm A, dedicated nurses provided information to pts, a daily record on which pts would take note of drugs and dosages and a telephone monitoring during the first two cycles of therapy. The primary outcome was the reduction in improper hospital accesses for grade 1–2 toxicity according to CTCAE v4.0. Results: Out of 432 randomised pts, 378 were analysed (184 pts in arm A and 194 in arm B). Hospital accesses were observed in 41 pts in arm A and in 42 pts in arm B (22.3% vs. 21.6%, respectively). No difference was detected in proportion of improper accesses between arm A and arm B (29.3% vs. 23.8%, respectively). Conclusions: Our experience failed to support the role of a specific home care nursing programme for pts taking oral chemotherapy. An improved attention to specific educational practice and information offered to pts can explain these results. Relevance to clinical practice: Our results underline the role of nurse educational practice and information offered to patients. A careful nurse information of patients about drugs is essential to reduce toxicities avoiding the opportunity of a specific home monitoring.